A novel label-free method to determine equilibrium dissociation constants of antibodies binding to cell surface proteins - Eilyn R. Lacy; Rupesh Nanjunda; Scott L. Klakamp; Deborah Kwok; Jennifer F. Nemeth; Gordon D. Powers; H. Hugo Caicedo; Steven A. Jacobs (Scientific Reports)
Abstract Solution-based affinity assays are used for the selection and characterization of proteins that could be developed into therapeutic molecules. However, these assays have limitations for cell-surface proteins as in most cases their purification requires detergent solubilization and are unlikely to assume conformations in solution that resemble their native states in cell membranes. This report describes a novel electrochemiluminescence-based method, called MSD-CAT, for the affinity analysis of antibodies binding to cell-surface receptors. MSD-CAT was used to evaluate the binding of monoclonal antibodies, Fab fragments, and bispecific antibodies targeting the cell-surface receptor interleukin 3 receptor alpha (CD123) and the results were compared to data obtained using surface plasmon resonance (SPR). The data showed that MSD-CAT can be successfully applied to determine binding affinity on cells in a label free format and without the need for laborious solubilization procedures to generate recombinant antigen. In addition, this method has the potential for high-throughput application while enabling simultaneous determination of equilibrium dissociation constant (KD) and receptor density within the same experiment.